Endogenous, Climate, and Fishing Influences on the Population Dynamics of Small Pelagic Fish in the Southern Humboldt Current Ecosystem - Canales, T. Mariella; Lima, Mauricio; Wiff, Rodrigo; Contreras-Reyes, Javier E.; Cifuentes, Ursula; Montero, José (Frontiers in Marine Science, 2020)
There remains a lack of holistic approaches for analyzing how different density-independent and density-dependent (endogenous) mechanisms interact to drive the dynamics of the small pelagic fish populations of the southern Humboldt Current ecosystem. In this study, we analyzed the drivers of the small pelagic fishes off the coast of Chile from the late 1980s until the early 2010s. We postulated that climate, fishing and endogenous effects drove the biomass dynamics of these populations. Per capita growth rates (R-models) were used to investigate how these factors regulated the dynamics of three anchovy populations and one population of common sardine off the Chilean coast. We found that the dynamics of the anchovy populations located off northern Chile were driven by endogenous components and by the effects of the climate, fishing and the climate-fishing interaction. We proposed that during the study period, the climate conditions favoured the population growth of the anchovies in the north; however, fishing had a negative effect on anchovy biomass, which was facilitated by the climate. The dynamics of the small pelagic fishes off central-southern Chile showed weaker endogenous effects. Indeed, the anchovy population displayed the lowest density-dependent effect, and fishing played the most significant role. The endogenous effect on the common sardine was slightly higher in comparison to that on the anchovies; however, climate (sea surface temperature) seemed to be the main driver of the flourishment in the common sardine biomass following 2006, which supported the previous hypothesis regarding the effect of climate on the species. We discussed that the R-models approach could be used to provide a holistic understanding of the drivers of the biomass dynamics of these populations. The approach provided a framework for integrating climate variability in the population dynamics of these species and moving towards an ecosystem approach to fisheries management. Further steps involve exploring the effects of competition and predation on the population dynamics of these species.